The effect of operational slack, diversification, and vertical relatedness on the stock market reaction to supply chain disruptions - Hendricks, Kevin B.; Singhal, Vinod R.; Zhang, Rongrong (Journal of Operations Management, 2009)
AbstractThis paper empirically examines whether operational slack, business diversification, geographic diversification, and vertical relatedness influence the stock market reaction to supply chain disruptions. The results are based on a sample of 307 supply chain disruptions announced by publicly traded firms during 1987–1998. Our analysis shows that firms with more slack in their supply chain experience less negative stock market reaction. The extent of business diversification has no significant effect on the stock market reaction. Firms that are more geographically diversified experience a more negative stock market reaction. We find that firms with a high degree of vertical relatedness experience a less negative stock market reaction. These results have important implications on how firms design and operate their supply chains to mitigate the negative effect of supply chain disruptions.